EZ-Arabic for children :a virtual learning resource tool for Malaysian primary schools - Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus; Nasir, Mohd Shahrizal (2012)
This innovation features a virtual Arabic learning tool prototype, which is specifically designed for learners at primary schools in Malaysia. The innovative process begun with the literature analysis of 3 theories based on the work of Nation (2003), Prensky (2001) and Mayer (2001). The design and development of this game-based learning prototype are modelled on the methods and approaches of design and development research (Richey & Klein, 2007) or formerly known as developmental research (Richey, Klein & Nelson, 2004). This method is also known as designed case (Reigeluth & Frick, 1999), design-based research (Reeves, 2006 & Herrington, et. al, 2007), formative research (Nieveen, 2007), and design research (Bannan-Ritland, 2003; Van der Akker, 2007). This prototype is designed and developed based on ‘design principles’ adapted from a study by Muhammad Sabri (2011), which was conducted on the design and development of an online Arabic vocabulary learning games prototype among pre-university learners in IIUM. This expanded Arabic virtual learning tool prototype enables teachers and students access to additional Arabic language learning aids, and complementing traditional learning methods. It facilitates Arabic learning enhancement through a compendium and variety of open-sources of learning tools such as the followings : a) E-book of Arabic text books, including extra reading story books, b) Educational Arabic games, c) Audio learning aids (MP 3) in Arabic, d) Visual learning aids (MP 4) in Arabic, e) Online dictionary and translator for Arabic, f) Online chat-box for virtual discussion and synchronous learning, g) Arabic keyboard for PC without stickers in Arabic letters, h) Links of various websites for learning Arabic for children, i) Other features to be updated from time to time. The prototype provides a new learning experience for students who have been through a traditional Arabic teaching and learning methods, by immersing into the attractive, interesting and interactive virtual learning environment. The prototype is still in its pilot phase of design and development by analysing the feedbacks from teachers and pupils from several selected teachers in Malaysian primary schools. The prospect potential market and use of this product are wide, it includes: schools, universities and other learning institutions, special programmes, eg: J-Qaf, KAFA, states religious schools, etc. The URL for this games prototype is http://ezarabic.net/v1/